Estudo in silico e in vitro da curcumina livre e nanoestruturada em células infectadas e não infectadas por Toxoplasma gondii - Copetti, Priscila Marquezan (2024)
Toxoplasmosis, a disease caused by the intracellular protozoan Toxoplasma gondii (T. gondii) affects several organs, including the central nervous system (CNS). The low therapeutic efficacy is related to the passage through the blood-brain barrier (BBB), the latent form of the parasite, as well as the side effects of conventional medications. Nanostructured systems can actively deliver substances to the CNS and improve the efficacy and therapeutic bioavailability of substances such as curcumin. This polyphenol has anti-inflammatory capacity and antioxidant properties that can mediate the inflammatory changes caused by T. gondii infection. However, its effectiveness is limited due to low water solubility and biodistribution and instability at specific pH that can be overcome with the use of nanotechnology. Curcumin nanocapsules can act on the immune response, modulating inflammatory, antioxidant and neuronal signaling pathways. Therefore, the objective was to investigate the pharmacokinetics and toxicity of curcumin in silico, as well as the influence of treatment with free curcumin and different nanostructured systems on the molecular mechanisms of signaling in cells exposed and not exposed to infection with T. gondii in vitro. The ADME/Tox profile of curcumin was generated using computational tools. Eudragit® L-100 and PCL nanocapsules were produced and characterized and then the hemolytic potential in erythrocytes was evaluated, as well as the cytotoxic capacity (MTT and dsDNA PicoGreen® assay) and influence on redox metabolism (production of nitric oxide and DCF) in peripheral blood mononuclear cells (PBMCs) and fibroblasts (HFF-1 cell line). Furthermore, in vitro cytotoxicity, redox metabolism and gene expression tests (IL-10, IL-1β, TNF-α, NRLP3, P2X7, A1 and A2A) were performed for microglial cells (BV-2 cell line) infected with T. gondii. The computational results for curcumin showed low biodistribution, lack of BBB permeation, slight gastrointestinal absorption, inhibitory potential of cytochrome P450 isoforms (CYP2C9 and CYP3A4), toxicity class IV and immunomodulatory action. In in vitro tests, treatments induced different cellular responses according to the types of cells used, CMSP showed a concentration-dependent pattern, while HFF-1 cells incubation time was an important variable. Redox interactions showed that the nanocapsules induced the production of nitric oxide and all treatments reduced the levels of reactive species. Microglial cells infected with T. gondii showed a cytotoxic effect of curcumin, which modulated inflammatory, oxidant and purinergic pathways through cell signaling in response to pro- and anti-inflammatory markers. Furthermore, the nanostructured systems increased response patterns to cell signaling when compared to the substance in free form. In general, the treatments positively modulated the immune response and purine-mediated cell signaling, interfering with T. gondii infection. It is noteworthy that pharmacological safety must always be evaluated for release systems, especially substances with multiple interaction pathways. Furthermore, nanostructured systems showed a better treatment response than the substance in free form. Therefore, nanostructured delivery models help so that therapeutic properties can be better utilized, especially in neuroinflammatory diseases.